FCSE at ImageCLEF 2012: Evaluating Techniques for Medical Image Retrieval - Kitanovski, Ivan; Dimitrovski, Ivica; Loshkovska, Suzana (My University, 2012)
. This paper presents the details of the participation of FCSE (Faculty of Computer Science and Engineering) research team in ImageCLEF 2012 medical retrieval task. We investigated by evaluating different weighting models for text retrieval. In the case of the visual retrieval, we focused on extracting low-level features and examining their performance. For, the multimodal retrieval we used late fusion to combine the best text and visual results. We found that the choice of weighting model for text retrieval dramatically influences the outcome of the multimodal retrieval. We tested the multimodal retrieval on data from ImageCLEF 2011 medical task and based on that we submitted new experiments for ImageCLEF 2012. The results show that fusing different modalities in the retrieval can improve the overall retrieval performance.
Keywords: Information Retrieval, Medical Imaging, Content-based Image Retrieval, Medical Image Retrieval